Boundedness of Fractional Integral Operators Containing Mittag-Leffler Function via Exponentially s-Convex Functions - Gang Hong; G. Farid; Waqas Nazeer; S. B. Akbar; J. Pečarić; Junzhong Zou; Shengtao Geng (Journal of Mathematics)
The main objective of this paper is to obtain the fractional integral operator inequalities which provide bounds of the sum of these operators at an arbitrary point. These inequalities are derived for s-exponentially convex functions. Furthermore, a Hadamard inequality is obtained for fractional integrals by using exponentially symmetric functions. The results of this paper contain several such consequences for known fractional integrals and functions which are convex, exponentially convex, and s-convex.